An exploration of goal-setting practices in Queensland rehabilitation services. Issue 16 (31st July 2022) - Baker, Amanda; Cornwell, Petrea; Gustafsson, Louise; Lannin, Natasha A.
Abstract: Background: Goals are vital in rehabilitation; however, how goal-setting occurs varies widely in clinical practice. This study aims to review goal-setting practices across the rehabilitation continuum within varied case mix services in Queensland, Australia. Method: A descriptive multisite qualitative case study with medical record audits and interviews of adult rehabilitation clients was used to evaluate four propositions across three inpatient and two community rehabilitation services. The propositions evaluated the process in which goal-setting occurs, action planning and review of goals, as well as the type, specificity and client-centeredness of goals set. Results: Goals ( n  = 1120) were often poorly defined, focussed on short term physical functioning and were predominantly set by individual disciplines with the client rather than using an interdisciplinary approach. Clients were not consistently given action plans to pursue goals ( n  = 59, 18%) and the review of goal progress ( n  = 60, 18%) was limited. Few clients reported receiving copies of their rehabilitation goals ( n  = 16, 25%). Conclusion: Goal-setting in rehabilitation should be specific, meaningful and include the client in action planning, feedback and review. However, goal-setting in rehabilitation is often multidisciplinary and unstructured. Implications for rehabilitation: Best-practice rehabilitation team goal-negotiation and goal-setting should include a common goal focus and incorporate components of staff and client action planning, coping planning, feedback and review. Rehabilitation clients prefer shared-decision making approaches to setting meaningful and personalised goals, however, require time and support to engage in the goal-setting and negotiation process. Rehabilitation clinicians need training and support to improve their goal negotiation and goal writing skills to create specific, understandable and meaningful goals with rehabilitation clients.